Nano-Selenium and Nano-Curcumin Supplementation Effect on Liver Function in Broiler Chickens - , H. S.Shwetha; M. Narayana Swamy; B. Srinivas Reddy, M. K.Vinuthan; A, SAHADEV; E, Preediya BABU; D, RAJENDRAN (Indian Journal of Animal Nutrition, 2023)
The present study was designed to compare the impact of dietary supplementation of nano-selenium and nano-curcumin on biochemical parameters response of broiler chickens. A total of 360 day-old broiler chicks were randomly divided into four groups with each group comprising 90 chicks. Group I chicks served as control with standard broiler diet. Groups II, III and IV were supplemented with nanoSe (0.3 mg/kg diet), nano-curcumin (200 mg/kg diet) and combination of both nano-Se (0.15 mg/kg diet) and nano-curcumin (100 mg/kg diet) along with basal diet, respectively. Blood samples were collected on 21st, 28th, 35th and 42nd day and processed for serum samples. Liver enzymes, glucose and total protein profile was estimated by using spectrophotometric method. Serum alanine transaminase (ALT) activities were significantly lower in supplemented groups compared to control groups. Significantly lower serum aspartate amino transferase (AST) activities were observed in Group III and Group IV when compared to Group I. Non-significant (P